Media Belajar Interaktif Untuk Anak Penyandang Disleksia Di Kota Palembang - Amalia Ainunnisa; Yosef Yulius; Husni Mubarat (VisArt: Jurnal Seni Rupa dan Design, 2024)
Reading disorders in children are the first step in children's education. Reading is an ability that everyone must have, reading is the key to opening up space for imagination and expanding the learning process which has an impact on the future of every child. This reading disorder is called Dyslexia. Dyslexia has an impact on children ranging from educational, social factors and can even disturb the child's psychology. The main problem faced is how to deal with children who experience dyslexia. The main aim of this design is to overcome children's delays in reading, writing and language at the age of 7-12 years. Children's difficulties in recognizing letters mean that visual communication design plays an important role in producing informative message solutions through color, layout and typography. To produce interactive and effective learning media in solving reading problems, the author uses the design thinking method, so that the resulting interactive learning media is able to increase the ability and motivation to learn to read for children with dyslexia and increase the public's insight into how to prevent dyslexia disorders in children aged 7- 12.